Sacha inchi as potential source of essential fatty acids and tocopherols: multivariate study of nut and shell - doi: 10.4025/actascitechnol.v35i4.19193 - Souza, Aloisio Henrique Pereira de; Gohara, Aline Kirie; Rodrigues, í‚ngela Cláudia; Souza, Nilson Evelázio de; Visentainer, Jesuí Vergílio; Matsushita, Makoto (Acta Scientiarum. Technology, 2013)
The present study investigated the fatty acid composition, tocopherols and nutritional factors in the nut and shell of Sacha inchi (Plukenetia volubilis) through multivariate data analysis. The nut showed a high lipid content (48.5%), while the shell showed a low content (1.2%), although both parts of the plant had similar fatty acid composition. Low contents of saturated fatty acids were found in both parts, indicating anti-atherogenic, anti-thrombogenic and hypercholesterolemic effects. The content of n-3 fatty acids (438.7 mg g-1 of total lipids) found in the nut corroborates with the literature, while the content found in shell (329.4 mg g-1) is not previously described. The total tocopherol content was higher than other oilseeds. The great amount of Î±-tocopherol present in the shell is highlighted since this is considered primarily responsible for the metabolic activity of vitamin E. Dietary Reference Intakes proved that both parts of Sacha inchi have a good nutritional supply. The use of multivariate analysis allowed nuts and shells to be distinguished and their constituents to be checked. The incorporation of Sacha inchi in the human diet is promising due to its intrinsic characteristics, as well as the use of the shell in food processing. Â